Media Flashcard Sebagai Sarana Edukatif Dalam Pembelajaran Kalimat Fakta Dan Opini Kelas IV Di SDN Model Mataram - Lilis Rizkiya Amanda; Lale Aulia Rizki Oktafiani; Muhammad; Ni Luh Tri Dewi Damayanti; Iin Juliana (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2025)
This learning activity was carried out on May 23, 2025 in class IV of SDN Model Mataram, with the aim of improving students' understanding in distinguishing factual and opinion sentences through the use of flashcard media. This implementation method includes three stages, namely planning, implementation, and evaluation. In the planning stage, namely compiling learning devices and designing flashcard media using the Canva application. The implementation is carried out through interactive learning with a Problem Based Learning approach that combines group discussions, presentations, and fact and opinion card games. Evaluation is carried out through observation of student activities, group work results, and completion of individual LKPD. The evaluation results show that the use of flashcard media significantly helps students understand the differences between factual and opinion sentences. Students become more active, enthusiastic, and motivated in participating in learning activities and learning becomes more fun and meaningful. It is hoped that flashcard media can continue to be used as an alternative innovative learning strategy to improve students' critical thinking skills in examining information.